Efficiency Improvement on a Distribution Feeder: A Case Study - Dhakal, Megha Nath; Ghimire, Rudra (Journal of the Institute of Engineering, 2020)
Electricity is a necessary requirement for accelerating the economic development of any country and is considered an important input to improve quality of life. Electricity supply to consumer end is possible by the combine function of power generation, transmission and distribution instantly. One of the most chronic areas of power loss in power system is power distribution feeder. Loss in feeders are identified mainly due to overloaded conductors and transformers, long distance feeder, unbalance load on transformer, low power factor load, uses of energy inefficient load, hooking etc. The distribution losses which are more predominant can be categorized as technical losses and non-technical losses. The main target of the study is to improve the technical and overall efficiency of a distribution feeder. A high loss feeder is selected for efficiency study. Direct method of loss calculation is used to calculate total losses of the feeder and indirect method is used to find the technical losses on the feeder in existing condition. Technical losses of existing feeder and improvement on same distribution system through technical loss reduction options is analyzed by implementing the conductor replacement, rerouting and optimum capacitor placement (OCP) methods using electrical transient analyzer program (ETAP) simulation. Technical efficiency and overall efficiency for the different non-technical loss values are calculated and analyzed. Implementation of results will improve financial health of the power distribution company and provide reliable electricity supply to the consumers. In addition, it provides further inputs to energy planners and managers for a number of remedial measures to loss reduction and improvement of overall efficiency of the power distribution system.